Dynamics of Islamic and Islamism Discourse: A Critical Analysis of Teti & Mura's Thoughts - Rahmat, Efendi; Sahid, Asep Abdul; Sukayat, Tata (UIN Sunan Gunung Djati Bandung, 2025)
This study critically interrogates the ideological construction underlying the distinction between “Islam” as a private spirituality and “Islamism” as a political threat within contemporary European discourse. By analyzing Chapter 7 of The Routledge Handbook of Critical European Studies, authored by Andrea Teti and Andrea Mura, the article explores how these categories are shaped by colonial legacies, power relations, and the normative framework of European secularism. Employing a qualitative method grounded in critical discourse analysis and Foucauldian genealogy, this research demonstrates that the Islam/Islamism binary functions as a hegemonic tool that disciplines Muslim political expression while reaffirming the epistemic supremacy of liberal modernity. Findings reveal that the depiction of Islamism as “radical” and inherently antagonistic is not an objective reflection of Muslim political realities, but rather a product of discursive practices that marginalize Muslim agency and render their political subjectivities illegible within the liberal-secular order. Furthermore, the study highlights the urgency of adopting emancipatory and decolonial perspectives that foreground the voices and experiences of Muslim communities themselves. Such approaches challenge Western monopolies on meaning and open epistemic spaces for alternative narratives. The study concludes that dominant Western discourses on Islam must be deconstructed through the development of critical, context-sensitive epistemologies that restore agency to Muslim political subjects. This research contributes to postcolonial studies, critical secularism theory, and contemporary Islamic political thought by offering a robust analytical framework to rethink the intersection of religion, politics, and power in a postcolonial age.